2021
DOI: 10.3389/fmicb.2021.632575
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation and Mixed Reproductive Strategies in the Northern Corn Leaf Blight Pathogen Setosphaeria turcica From Sweet Corn in Fujian Province, China

Abstract: The northern corn leaf blight (NCLB) pathogen Setosphaeria turcica (Luttrell) Leonard and Suggs is one of the main biotic constraints on sweet corn (Zea mays L.) yield and quality in Fujian Province, China. Currently, however, there is comparatively little information available regarding the distribution of mating types, population genetics, and reproductive strategies of this pathogen in Fujian. In this study, we investigated the distribution of mating types and population genetics of 117 isolates of S. turci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…In this study, we identified a relatively high level of gene flow (6.2385) of S. turcica isolates between Henan and Shanxi, indicating frequent gene exchange between these two populations. The value of Fst between Henan/Shaanxi (0.1573) and Shanxi/Shaanxi (0.1202) was greater than Henan/Shanxi (0.0385), demonstrating relatively moderate genetic divergence between these populations, which was lower than that previously reported by Dai et al (2021) . In addition, the result of the AMOVA analysis demonstrated the genetic variation within populations, rather than those between populations, was the major source of genetic variation, which was consistent with previous reports by Li et al (2019) and Ma et al (2020a) .…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…In this study, we identified a relatively high level of gene flow (6.2385) of S. turcica isolates between Henan and Shanxi, indicating frequent gene exchange between these two populations. The value of Fst between Henan/Shaanxi (0.1573) and Shanxi/Shaanxi (0.1202) was greater than Henan/Shanxi (0.0385), demonstrating relatively moderate genetic divergence between these populations, which was lower than that previously reported by Dai et al (2021) . In addition, the result of the AMOVA analysis demonstrated the genetic variation within populations, rather than those between populations, was the major source of genetic variation, which was consistent with previous reports by Li et al (2019) and Ma et al (2020a) .…”
Section: Discussioncontrasting
confidence: 67%
“…Moderate level of genetic diversity in these three population was found as indicated by Shannon’s information index (0.51–0.57), which is somewhat incongruent with previous studies on the genetic diversity of S. turcica isolates. Ma et al (2020a) and Dai et al (2021) , respectively, attained low Shannon’s information index of 0.20 to 0.37 and 0.07 to 0.33, indicating low genetic diversity among different populations. Whereas Human et al (2016) and Nieuwoudt et al (2018) both achieved high level of genetic diversity with Shannon’s information index of 0.87 to 0.90 and 0.66 to 0.94.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conical flasks with 2% potato dextrose broth were used to culture E. turcicum isolates for 10 days at 26 ± 2 °C. A few changes to the modified CTAB procedure [ 21 , 22 ] were made in order to extract DNA from the growing mycelial mats. Using liquid nitrogen, the collected fungus mats were ground into a fine powder.…”
Section: Methodsmentioning
confidence: 99%